THE USE OF COMMUNICATIVE LANGUAGE IN ISLAMIC RELIGIOUS EDUCATION LEARNING - Edhy Rustan; Fitriani Fitriani (Edukasi Islami : Jurnal Pendidikan Islam, 2020)
Effective learning information that is easily understood by students. So the use of communicative language becomes an important topic in learning without exception Islamic religious education. This article discusses the use of communicative language, influential factors, and communicative language needed in the learning of Islamic religious education. Descriptive qualitative data was collected through observation, interviews, documentation, and recording/video. Sources of research data are Islamic religious educators and students in SMP Negeri 5 Palopo. Data were analyzed using an interactive analysis model of Miles and Huberman which divided into data collection, data reduction, data presentation and conclusion drawing. The researchers' findings show that the use of communicative language in the teaching of Islamic education is quite good and the factors that influence the use of communicative language are internal and external factors originating from educators, students, and the availability of facilities and infrastructure. Communicative language needed in Islamic religious education learning is communicative language that is easily understood by students, interspersed with the use of local languages, uses appropriate media and teaching aids and takes into account the condition of students while still referring to the communicative competencies that teachers need to have.